Lartetium africanum (Lavocat, 1961) (Eulipotyphla center dot Soricidae) from Beni-Mellal (Morocco), the oldest African shrew: new descriptions, palaeoenvironment and comments on biochronological context - (:unkn) unknown (My University, 2015)
Additional specimens of the poorly known African shrew Lartetium africanum (Lavocat, 1961) are described and complete our knowledge of this tiny animal. The results of this study justify the elevation of material originally described as a subspecies to the species rank. Soricids are hitherto unknown in older African localities. Like many other soricids, L. africanum lived in a rather humid habitat, close to a body of freshwater, as testified by the intercalations of travertines with reeds in the lacustrine lenses that yielded the fauna. However, the presence of associated vertebrate taxa also attest to more open environments in the surroundings and a tropical climate. Various hypotheses on the date of arrival of this taxon in Africa have been proposed since migration routes between Eurasia and Afro-Arabia were not always open during the Middle Miocene and also because magnetostratigraphic data are now known and can be compared. These hypotheses are discussed here. Recent advances in our knowledge of the palaeogeography and the comparison of L. africanum with western European Lartetium taxa suggest that Beni-Mellal could be older than previously proposed, possibly early Middle Miocene.
Keywords: African Research